(untitled) (Applied Biological Research, 2025)
The most frequent forms of α- and β-degenerate anaemias are characterized by disruption in the formation of globin protein, leading to defective hemoglobin synthesis known as thalassemia, a prevalent hereditary blood disorder. The present study aimed to diagnose hemoglobin A₂ (HbA₂) levels in patients with thalassemia in order to provide a reference for improving thalassemia control strategies. Data were collected from 155 thalassemia patients attending Baghdad Medical City between November 2024 and March 2025. Hematological parameters including red blood cell count (RBC), hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), hemoglobin A (HbA), hemoglobin A₂ (HbA₂), and fetal hemoglobin (HbF) were analyzed, and relationships among these parameters were evaluated. High-performance liquid chromatography (HPLC) results showed that thalassemia patients had significantly higher mean levels of HbA₂, HbA, and HbF (P ≤ 0.01) compared with the control group. Correlation analysis revealed no significant association between serum ferritin and RBC count in the HbA₂ patient group (P ≤ 0.01). The findings indicate that individuals with β-thalassemia trait typically exhibit normal serum ferritin levels, mildly elevated red blood cell counts, and increased HbA₂ levels.